A new Manayunkia species (Polychaeta: Sabellida: Fabriciidae) from the lakes of the Kolyma and Ola River basins (Northeastern Asia, Russia) - Gagaev, Sergey; Regel, Kira; Teterina, Veronika; Sitnikova, Tatiana (Zootaxa, 2025)
A new fabriciid species, Manayunkia kolhymensis sp. nov., has been described from Lakes Namakanskie (Oymyakonskie) of the Kolyma River basin and Serdyakhskie of the Ola River basin in Russia. The worms were collected from sunken wood at a depth of about 1 m, where they formed colonies of transparent tubes covered by mud particles. Some tubes contained up to 6–7 developing embryos. The new species slightly differs in the morphological characters from the close genetically relative M. occidentalis Atkinson, Bartholomew & Rouse, 2020 inhabiting north-western American fresh water rivers. The description of the new species is accompanied by COI barcode data.